Linking nitrogen-rich organic cages into isoreticular covalent organic frameworks for enhancing iodine adsorption capability - Cheng, Ke (2023)
By linking a nitrogen-rich organic cage with linear connectors, three cage-based isoreticular covalent organic frameworks, i.e., Cage-IRCOF-1, Cage-IRCOF-2, Cage-IRCOF-3, were successfully designed and synthesized by Schiff-base polycondensation reactions. The structure determination and simulations from powder X-ray diffraction measurements indicated that these COFs have high crystallinity derived from the packing of covalently linked two-dimensional isoreticular layer frameworks. As nitrogen-rich porous materials, iodine capture studies were carried out, proving that they displayed obvious enhancements in iodine uptake as compared with the pristine cage itself. In particular, Cage-IRCOF-1 displayed an iodine adsorption capacity of 262 wt %, which is 12 times higher than the solid packed from the cage itself. Spectral studies revealed that there were strong interactions between the nitrogen-rich groups and the adsorbed iodine species. This work demonstrated that linking the discrete organic cages into reticular crystalline frameworks, effective adsorbents can be fabricated for targeted applications.